Loading

Solve simultaneously x + y = 1, 2x + 3y =9

To solve this problem I would begin by rearranging the first equation to equal X.1) x + y = 1 -> x = 1 - yI would then substitute this into the second equation.2) 2x + 3y = 9 -> 2(1-y) + 3y = 9Then multiply out the bracket.3) 2(1-y) + 3y = 9 -> 2 - 2y + 3y = 9Simplify.4) 2 - 2y + 3y = 9 -> 2 + y = 9Solve. 5) 2 + y = 9 -> y = 7resubstitute this into the first equation and solve.6) x + y = 1 -> x + 7 = 1 -> x = -6which gives you the final solution of X = -6 and y = 7.

Answered by Isabel C. Maths tutor

161 Views

See similar Maths GCSE tutors
Answered by Isabel C.
Maths tutor

161 Views

See similar Maths GCSE tutors
A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.

A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.

A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.